Republic of Uzbekistan : Improving Early Childhood Care and Education - World Bank (Washington, DC, 2013)
Uzbekistan is a lower middle-income country of 29.5 million people, located in Central Asia, with an economy that has been growing by over 8 percent per annum since the mid-2000s. Given international evidence about the high returns that can be realized from investing in pre-primary education ranging from promoting children s school readiness to equalizing opportunities across the income distribution, policymakers are keen to explore ways to expand access and promote the provision of high-quality early childhood education. This report is divided into four sections. Section two presents an analytical framework for analyzing early childhood interventions. Section three conducts an in-depth analysis of Early Childhood Care and Education (or Pre-primary Education), or ECCE in Uzbekistan, with a focus on increasing access and equity, promoting quality, and ensuring adequate and effective financing. Section four makes some recommendations for expanding access to high-quality ECCE in Uzbekistan.